Not Only Environmental Conditions but Also Human Awareness Matters: A Successful Post-Crayfish Plague Reintroduction of the White-Clawed Crayfish (Austropotamobius pallipes) in Northern Italy - Manenti, Raoul; Barzaghi, Benedetta; Nessi, Alessandro; Cioccarelli, Sara; Villa, Mauro; Ficetola, Gentile Francesco (Frontiers in Ecology and Evolution, 2021)
In Europe, invasive freshwater crayfish are not only changing freshwater ecosystems, but they are also leading to local extinctions of native freshwater crayfish. This is particularly evident for the populations of red swamp crayfish and spiny-cheek crayfish in northern Italy, which are threatening the last and isolated populations of the white-clawed crayfish. Here, we describe the steps that accompanied a successful reintroduction of the white-clawed crayfish in an Italian stream (Park Monte Barro) that, although isolated from other freshwater sites, suffered from an illegal introduction of the spiny-cheek crayfish in 2013. After the removal of presumably all the introduced spiny-cheek crayfish individuals, we started periodical surveys (twice a year) of the stream to confirm the absence of further introductions and to monitor environmental conditions. Prior to the reintroduction of the white-clawed crayfish that started in autumn 2018, we developed an intense dissemination activity to raise awareness of white-clawed crayfish features and importance among landowners surrounding the stream, including those suspected of the introduction of the spiny-cheek crayfish: we organized public meetings and we performed seven direct visits, house to house, to the local people providing information on good practices for white-clawed crayfish conservation. From 2018 to 2020, every autumn, we reintroduced a batch of 3-month-old white-clawed crayfish juveniles, and we developed a program for the monitoring of crayfish growth and density, water quality, and direct landowners’ disturbance of the site. We detected a significant increase of the white-clawed crayfish total length (TL) from the first reintroduction (October 2018) to June 2020. In 2020, crayfish were consistently larger than in the 2019 surveys; some of them were able to breed less than 2 years after the first reintroduction. In 2020, the estimated density of large crayfish reached 0.57 individuals/m2, which is lower than the density observed prior to extinction. We did not detect any case of human disturbance of the site. Our results underline that the reintroduction actions could be more effective when the stakeholders having the greatest potential impact on the species are identified, informed, and involved as primary caretakers of the activities.